2023
DOI: 10.1021/acsami.2c22162
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Transport Mechanisms in Graphene Nanoplatelet Doped Polydimethylsiloxane and Application to Ultrasensitive Temperature Sensors

Abstract: The temperature effect on electronic transport mechanisms in graphene nanoplatelet (GNP) doped polydimethylsiloxane (PDMS) for temperature sensing applications has been investigated under electrical impedance spectroscopy (EIS) analysis. AC measurements showed a very prevalent frequency-dependent behavior in low filled nanocomposites due to the lower charge density. In fact, 4 wt % GNP samples showed a nonideal capacitive behavior due to scattering effects. Therefore, the standard RC-LRC circuit varies with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…One of the factors contributing to the disparity between BET surface area and ECSA was proved to be the distinct electrical conductivity exhibited by various materials. 38 Since carbon-based materials are recognized for their high electrical conductivity, 39,40 there must be factors beyond electrical conductivity that contribute to this discrepancy. Previous studies have shown that the surface chemistry of carbon materials, particularly the presence of OFGs, plays a crucial role in their double-layer capacitance.…”
Section: Resultsmentioning
confidence: 99%
“…One of the factors contributing to the disparity between BET surface area and ECSA was proved to be the distinct electrical conductivity exhibited by various materials. 38 Since carbon-based materials are recognized for their high electrical conductivity, 39,40 there must be factors beyond electrical conductivity that contribute to this discrepancy. Previous studies have shown that the surface chemistry of carbon materials, particularly the presence of OFGs, plays a crucial role in their double-layer capacitance.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the behavior of PTC-type sensors in PVDF/ AgNW nanocomposites is explained by the volume expansion of the polymer matrix, since it promotes a reduction of electrical contacts between conductive nanoparticles [216,217]. In addition, the PDMS/graphene sensors also indicated PTC behavior by improving phonon/charge carrier dispersion, as well as by reducing the mean free path of charge carriers with increasing temperature [217,218].…”
Section: Temperaturementioning
confidence: 99%
“…For example, the behavior of PTC-type sensors in PVDF/ AgNW nanocomposites is explained by the volume expansion of the polymer matrix, since it promotes a reduction of electrical contacts between conductive nanoparticles [216,217]. In addition, the PDMS/graphene sensors also indicated PTC behavior by improving phonon/charge carrier dispersion, as well as by reducing the mean free path of charge carriers with increasing temperature [217,218]. However, other nanocomposites revealed NTC-like performance due to the formation of new conductive networks when exposing the nanocomposites to higher temperatures, or due to the nature of the matrix, which can sometimes show increased electrical conductivity due to ion transport [219].…”
Section: Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…In recent times, a lot of interest has been shown in GNPs as a potential filler material, which are essentially ultrathin sheets of carbon arranged in a honeycomb-like structure. The GNPs have notable properties such as excellent electrical conductivity (10 7 S m −1 ) [18], high stiffness, superior heat transfer, and a high surface area [19]. Carbon black is also known for its high surface area, lightness, and electrical conductivity (10 2 S m −1 ).…”
Section: Introductionmentioning
confidence: 99%